Genetic dissection of stem and leaf rachis prickles in diploid rose using a pedigree-based QTL analysis - Rawandoozi, Zena J.; Barocco, Andrew; Rawandoozi, Maad Y.; Klein, Patricia E.; Byrne, David H.; Riera-Lizarazu, Oscar (Frontiers in Plant Science, 2024)
Prickles are often deemed undesirable traits in many crops, including roses (Rosa sp.), and there is demand for rose cultivars with no or very few prickles. This study aims to identify new and/or validate reported quantitative trait loci (QTLs) associated with stem and rachis prickle density, characterize the effects of functional haplotypes for major QTLs, and identify the sources of QTL-alleles associated with increased/decreased prickle density in roses. Using a pedigree-based analysis (PBA) of two multi-parental diploid rose populations (TX2WOB and TX2WSE), 12 QTLs were identified on linkage groups (LGs) 2, 3, 4, and 6. The major QTLs for the stem prickle density were located between 42.25 and 45.66 Mbp on chromosome 3 of the Rosa chinensis genome assembly, with individual QTLs explaining 18 to 49% of phenotypic variance (PVE). The remaining mapped QTLs were minor. As for the rachis prickle density, several QTLs were detected on LG3, 4, and 6 with PVE 8 to 17%. Also, this study identified that ancestors R. wichurana ‘Basye’s Thornless’, ‘Old Blush’, and the pollen parent of M4-4 were common sources of favorable alleles (q) associated with decreased prickle density, whereas ‘Little Chief’ and ‘Srche Europy’ were the source of unfavorable alleles (Q) in the TX2WOB and TX2WSE populations, respectively. The outcomes of this work complement other studies to locate factors that affect prickle density. These results can also be utilized to develop high-throughput DNA tests and apply parental selection to develop prickle-free rose cultivars.